English English - Adrian Hidayat (Komunitas Dosen Indonesia, 2020)
This current Pandemic situation makes all the usual business become upnormal, including in the Banking System in Indonesia. Since a few years ago, due to Digital Economy makes changes in every economic sector all over the world including in Indonesia. Digitalization changes peoples how to buy and how to pay in the digital market, and therefore the government has to build the payment regulation according to the risk appetite, and control it for good for the both sides sellers and buyers. This new regulation will be launched effectively on July, 2021. New Regulation on Payment System by Central Bank of Indonesia, this will be the study on this journal.